CALCULATION OF THE EXACT INTEGRAL BY THE MONTE CARLO METHOD - Tajiyev Tahirjon Halimovich; Khusanov Azizjon Abdurashidovich; Samijonov is the son of Azizbek Ismailjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The most important aspect of constructing Monte Carlo methods is to reduce the problem to the calculation of mathematical expectations. Since mathematical expectations are often simple integrals, the central place in the theory of the Monte Carlo method is occupied by methods of calculating integrals.